Інноваційне лідерство та корпоративна культура як інструменти ефективного менеджменту - Лебедєва, Наталія Андріївна (My University, 2024)
У науковій роботі досліджується аналіз та застосування інструментів ефективного менеджменту, їх ключова роль для формування та сталого розвитку конкурентоспроможності організацій. Проаналізовано виклики, з якими стикаються лідери в умовах глобалізації, технологічних змін та кризи. Визначено роль емоційного інтелекту, адаптивного мислення та інноваційних підходів у забезпеченні ефективного лідерства в організаціях. Досліджено, що успішне лідерство стимулює інновації та забезпечує організаційну стабільність у нестабільному середовищі. Запропоновано рекомендації щодо підвищення ефективності управлінських рішень в умовах сучасних викликів шляхом впровадження нових підходів до розвитку корпоративної культури, лідерських навичок, зокрема емоційної компетентності та управління змінами. The scientific work examines the analysis and application of effective management tools, their key role in the formation and sustainable development of the competitiveness of organizations. The challenges faced by leaders in the conditions of globalization, technological changes and crisis are analyzed. The role of emotional intelligence, adaptive thinking and innovative approaches in ensuring effective leadership in organizations is defined. Successful leadership has been shown to help build team trust, drive innovation, and provide organizational stability in a volatile environment. Recommendations are offered to improve the effectiveness of management decisions in the face of modern challenges by introducing new approaches to the development of leadership skills, in particular, emotional competence and change management. One of the key challenges of modern leadership is the need to manage diverse teams, often in international or multicultural contexts. Emotional intelligence becomes especially important in such conditions, because it allows a leader to better understand cultural differences and adapt his management style according to the needs of different groups. Emotional intelligence is an important element for resolving conflicts and building constructive negotiations. Leaders who develop this skill can reduce stress levels in organizations, prevent burnout among employees, and increase overall job satisfaction. This is especially true in today’s business environment, where rapid changes and a high level of competition often cause stress for employees. Modern leaders must pay attention to their own personal development and learn to manage their emotions. This includes practices such as reflection, active listening, and developing empathic and communication skills. Thanks to constant selfimprovement, leaders will be able to motivate their teams more effectively, increase work productivity and create conditions for the sustainable development of organizations. Innovation and emotional intelligence are becoming important components of modern leadership, as they help leaders adapt to changes and establish effective interactions with teams. They provide leaders with the ability to effectively manage, taking into account the emotional needs and stimulating the personal and professional development of their team. In crisis situations, such as economic and social upheavals, leaders capable of bold decisions play a special role. Leaders must be ready to make difficult decisions and take responsibility for the outcome. Leadership in crisis requires managers not only professional skills, but also strong psychological stability and the ability to act in difficult, often unpredictable situations. In times of crisis, leaders must take responsibility for the risks that accompany every decision.
Лебедєва Н. А. Інноваційне лідерство та корпоративна культура як інструменти ефективного менеджменту / Н. А. Лебедєва // Держава та регіони. Серія: Економіка та підприємництво. - 2024. - № 3 (133). - С. 71-75. Режим доступу: https://doi.org/10.32782/1814-1161/2024-3-10
Keywords: лідерство; емоційний інтелект; управління змінами; інновації; глобалізація; кризове лідерство; цифрові технології; leadership; emotional intelligence; change management; innovation; globalization; crisis leadership; digital technologies